Musculoskeletal disorders among secondary school teachers in Douala, Cameroon: The effect of the practice of physical activities - Mekoulou Ndongo, Jerson; Bika Lele, Elysée Claude; Guessogo, Wiliam Richard; Meche, Laurence Patricia; Ayina Ayina, Clarisse Noel; Guyot, Jessica; Zengue, Babette; Lobe Tanga, Marie Yvonne; Owana Manga, Léon Jules; Temfemo, Abdou; Barth, Nathalie; Bongue, Bienvenu; et al. (Frontiers in Rehabilitation Sciences, 2022)
Introduction Musculoskeletal disorders (MSDs) represent an important threat to public health in both developed and developing countries, and are present in many occupational sectors including education. Regular practice of physical activity (PA) is known elicit preventive effects on the occurrence of MSDs. Objective This study aimed at determining the prevalence of MSDs and the preventive impact of PA on their occurrence among secondary school teachers. Participants and Methods A cross-sectional study was conducted among 179 teachers in five government secondary schools in Douala, Cameroon. The Nordic and Ricci-Gagnon questionnaires were used to determine MSDs and to assess the level of PA, respectively. Results The 12-month and 7-day prevalence of MSD (PMSD-12m and PMSD-7d) were 84.3% and 69.3%, respectively. The most affected body regions by MSDs were neck (PMSD-12m = 54.2%, PMSD-7d = 33.5%), lower back (PMSD-12m = 43%, PMSD-7d = 33%), and shoulders (PMSD-12m = 35%, PMSD-7d = 22.9%). Compared to female, males were protected against MSDs during the last 12 months (OR = 0.37; 95% CI 0.16–0.93; p = 0.04). The risk of MSDs during the last seven days was higher in teachers aged 30-40 years (OR = 2.86; 95% CI 1.14–7.14; p = 0.02) and 40-50 years (OR = 4.28; 95% CI 1.49–16.29; p = 0.008) than those under 30 years. This risk was tripled in inactive teachers (OR = 3.07; 95% CI 1.40–6.78; p = 0.005), compared to their active counterparts. Conclusion MSDs are prevalent among secondary school teachers and associated with aging, gender, and lower level of PA